2002
DOI: 10.1159/000065272
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Role of Brain Natriuretic Peptides in Hemodialysis Patients

Abstract: Background: Although plasma concentrations of brain natriuretic peptides (BNP) increase in hemodialysis (HD) patients as well as patients with cardiovascular diseases (CD), the clinical significance of BNP in HD patients has yet to be elucidated. In this study, we investigated the pathophysiological significance of BNP in HD patients. Methods: Plasma BNP concentrations were measured in 164 HD patients after HD and 14 healthy volunteers. In 12 patients without CD, BNP was also measured before HD. Multiple regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
96
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 26 publications
15
96
2
2
Order By: Relevance
“…Furthermore, BNP was found to be a significant independent predictor of cardiac death in haemodialysis patients with and without diabetes [29]. In the present study, for the first time, NT-proBNP was shown to be a strong predictor of mortality and cardiovascular mortality in type 1 diabetic patients with early diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, BNP was found to be a significant independent predictor of cardiac death in haemodialysis patients with and without diabetes [29]. In the present study, for the first time, NT-proBNP was shown to be a strong predictor of mortality and cardiovascular mortality in type 1 diabetic patients with early diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 59%
“…These results agreed with Naganuma et al who reported that high plasma BNP concentrations in HD patients were associated with volume overload [3]. Also Nishikimi et al concluded that plasma BNP levels were closely associated with the amount of extracellular water and the overhydration status in hemodialysis patients [14].…”
Section: Discussionsupporting
confidence: 89%
“…High plasma BNP concentrations in HD patients were associated with volume overload, left ventricular hypertrophy, cardiovascular disease and DM. Plasma BNP concentration may be a useful parameter for assessing the risk of cardiac death in HD patients by providing prognostic information independently of other variables previously reported [3]. In this study we tried to find out a cut off value for BNP in hemodialysis patients with fair cardiac function which indicates concealed volume overload that need revision of post-dialysis dry weight to preserve cardiac function and reduce the risk of cardiovascular mortality on the long term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when BNP was entered in a multivariate model, the relative risk for mortality was lower than that predicted by C-reactive protein or left ventricular mass. 38 Similarly, Cataliotti and coworkers 39 reported that BNP was significantly higher in dialysis patients who died of cardiovascular causes compared with survivors and was significantly associated with greater risk of cardiovascular death. In addition, a recent study found that NTproBNP predicts mortality in patients with endstage renal disease receiving hemodialysis.…”
Section: End-stage Renal Disease and Dialysismentioning
confidence: 96%